PENGUKURAN BEBAN KERJA DENGAN MENGGUNAKAN METODE RATING SCALE MENTAL EFFORT - Sari, Santika; Nuralma, Aliza; Feocliamsyah, Axel Rajiv; Hafiizh, Handy; Sunardi, Putri Elmiranda (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
In Indonesia, education can’t be separated from the role of teachers. Teachers have many responsibilities even with less welfare. Based on these problems, this study aims to measure the mental workload, analyze the factors that most influence it, and analyze improvement plans for teachers at SMP XYZ. The researcher uses a subjective workload measurement method in the form of a Rating Scale Mental Effort which only one measurement dimension is in the form of mental effort so that it is practical to use. The results showed that the value of the mental workload of teachers at SMP XYZ with the RSME method was 88.33 or the effort made tended to approach a fairly large scale. The most influencing factors are the difficulty of adapting learning to online, students do not have supporting devices, a lot of online learning preparation, and students who are late in collecting both assignments and remedial. Therefore, the improvement design that can overcome this is to provide online training and work guidance, facilitate mobile phone and internet quota assistance to students in need, provide students with project-based assignments that aren’t incriminating and fun, and proactively contact students and play the role of parents to assist online learning.